Analisis Bahan Ajar Bahasa Arab Siswa Kelas VII MTs Raudlatul Ulum Guyangan Pati Perspektif ‘Abdurraḥmān Al-Fawzān - Haning Rofi'ah (Alsina : Journal of Arabic Studies, 2022)
Teaching materials are a very important tool in learning, with the existence of materials the teacher is no longer the focal point and main source for students. Thus, the teacher is no longer burdened with complete mastery of the material or teaching materials, because students can learn independently with the existence of teaching materials or materials. This study will analyze the teaching materials for class VII Junior high school Raudhatul 'Ulum Guyangan Trangkil Pati using the perspective of 'Abd al-Raḥmān Ibn Ibrāhīm al-Fawzān. This study uses a qualitative library research method. The result of this study is that the teaching materials of Madrasah Tsanawiyah Raudlatul Ulum Guyangan Trangkil Pati are mostly in accordance with the expectations of 'Abd al-Raḥmān Ibn Ibrāhīm al-Fawzān but there are some things that are not according to the theory of 'Abd al-Raḥmān Ibn Ibrāhīm al-Fawzān. The limitation of this research is that the research does not include an analysis of the results of the use of teaching materials at Junior high school Raudhatul 'Ulum Guyangan Trangkil Pati.